Radiofrequency versus cryoballoon ablation for atrial fibrillation in the setting of left common pulmonary veins. Issue 11 (10th October 2019) - Coutiño, Hugo‐Enrique; Ströker, Erwin; Takarada, Ken; Mugnai, Giacomo; Abugattas, Juan‐Pablo; Sieira, Juan; Salghetti, Francesca; Terasawa, Muryo; Varnavas, Varnavas; Maj, Riccardo; Osório, Thiago Guimarães; Neach, Diego; et al.
Abstract: Background: A left common pulmonary vein (LCPV) accounts as the most frequent pulmonary vein (PV) variation. Our aim was to compare the performance of radiofrequency (RF) versus second‐generation cryoballoon (CB‐A) ablation in patients with atrial fibrillation (AF) and LCPVs. Methods: In a total cohort of 716 patients undergoing PV isolation with preprocedural CT‐scanning, LCPV+ patients were selected with measurement of PV ostial area and trunk distance. All LCPV+ patients were matched between RF and CB‐A group in a 1:1 ratio based on propensity scores, and compared for outcome. Results: Left common pulmonary veins were found in 31% (88/283) RF versus 34% (146/433) CB‐A patients, respectively, ( P  = .44). In the matched population of 83 LCPV+ patients in each group, electrical isolation could be achieved in all left‐sided PVs. No significant difference was noted for the rate of AF/left atrial tachyarrhythmia (LAT) recurrence between RF and CB‐A group (30% vs 28%, P  = .86), with similar AF/LAT‐free survival (log rank, P  = .71). There were 48 patients with AF/LAT recurrence (29%) during the follow‐up. Recurrence rate between paroxysmal versus persistent AF was 27/120 (22.5%) versus 21/46 (46%), P  = .004. Cox proportional regression analysis withheld LA volume and persistent AF as independent variables to predict AF/LAT recurrence. No increased hazard for AF/LAT recurrence was observed for patients with a long (>15 mm) vs short (5‐15 mm) LCPV trunk (OR 1.14, 95% CI 0.6‐2.2, P  = .7). Conclusions: In our study, equal efficacy and outcome was noted in LCPV+ patients between RF and CB‐A technology.